2005
DOI: 10.3758/bf03195332
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory and the attentional blink: Capacity versus content

Abstract: When people monitor the rapid serial visual presentation (RSVP) of stimuli for two targets (T1 and T2), they often miss T2 if it falls into a time window of about half a second after T1 onset, a phenomenon known as the attentional blink (AB). We found that overall performance in an RSVP task was impaired by a concurrent short-term memory (STM) task and, furthermore, that this effect increased when STM load was higher and when its content was more task relevant. Loading visually defined stimuli and adding artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
37
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 27 publications
11
37
1
Order By: Relevance
“…This implies that STM capacity is a factor that plays a role only after targets have been successfully selected from the RSVP stream, contrary to some of the existing attentional blink theories, which assign a pivotal role to STM in causing the blink (Chun & Potter, 1995;Jolicoeur & Dell'Acqua, 1998;Shapiro et al, 1997). In further support of this, Akyu¨rek and Hommel (2005) showed that when observers were given a STM task in addition to the RSVP task, target detection deteriorated with increasing memory load. However, this was an overall effect across the RSVP stream; memory load did not interact with lag.…”
Section: Discussioncontrasting
confidence: 45%
“…This implies that STM capacity is a factor that plays a role only after targets have been successfully selected from the RSVP stream, contrary to some of the existing attentional blink theories, which assign a pivotal role to STM in causing the blink (Chun & Potter, 1995;Jolicoeur & Dell'Acqua, 1998;Shapiro et al, 1997). In further support of this, Akyu¨rek and Hommel (2005) showed that when observers were given a STM task in addition to the RSVP task, target detection deteriorated with increasing memory load. However, this was an overall effect across the RSVP stream; memory load did not interact with lag.…”
Section: Discussioncontrasting
confidence: 45%
“…In a recent study, Akyürek and Hommel (2005) investigated the effects of short-term memory load on the attentional blink in a design very similar to the design we used in Experiment 1. The rationale of their experiments was that if attentional blink performance depends on short-term memory processes (as is held by some existing theories), then memory load should affect the magnitude of the attentional blink.…”
Section: Relation To Other Findingsmentioning
confidence: 99%
“…However, the studies have not obtained consistent results. In particular, some have found that although overall performance in RSVP tasks was impaired by a concurrent memory task, the attentional blink effect was little changed (Akyürek & Hommel, 2005. Likewise, Nieuwenstein, Johnson, Kanai, and Martens (2007) also found similar AB effects under memory load conditions, although they found stronger interference when information in WM fitted T2 in the RSVP (Experiment 2).…”
Section: Introductionmentioning
confidence: 89%
“…In the first experiment, the participants have to identify one target in an RSVP stream, while maintaining some information in working memory. According to Nieuwenstein et al (2007) (see also Akyürek & Hommel, 2005), we should find worse RSVP performance for those trials where memory contents are related to the target in the RSVP. That is, when similar memory information ''competes'' for different tasks (memory task vs. RSVP task), there is impairment on the attentional selection in the form of an error.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation